Biomass and physiological responses of green algae and diatoms to nutrient availability differ between the presence and absence of macrophytes - Hao, Beibei; Wu, Haoping; You, Jiaqi; Xing, Wei; Cai, Yanpeng (Ecological indicators, 2021)
[Display omitted] •Both phytoplankton Chl-a and Fv/Fm respond significantly to nutrient*macrophytes.•Macrophytes influence the response mechanism of phytoplankton to nutrient.•Responding mechanism differed between diatoms and green algae.•Combined use of physiological status and biomass provide greater insights. Nutrient enrichment commonly promotes phytoplankton biomass, while the presence of macrophytes can mitigate the promotion effects of nutrient loading. However, the existing studies have seldomly focused on the impacts of macrophytes on the phytoplankton’s physiological responses to nutrient availability. To fill this gap, a 30-day mesocosm experiment was conducted across a four-level nutrient gradient to investigate the variations of the phytoplankton biomass and physiological status (represented by Chl-a and Fv/Fm, respectively) in the absence and presence of macrophytes. Among the eight treatments, the performances of green algae and diatoms were compared as they accounted for >95% of the total phytoplankton biomass. Our results showed that although the presence of macrophytes did not inhibit Chl-a and Fv/Fm of green algae and diatoms, it significantly changed the effects of nutrients on Chl-a and Fv/Fm of green algae and diatoms. Structural equation model (SEM) indicated that the causal relationships between environmental variables and Chl-a/Fv/Fm of green algae and diatoms differed in the absence and presence of macrophytes. When macrophytes was absent, Chl-a and Fv/Fm of green algae and diatoms were significantly affected by electrical conductivity, TN, and Kd/salinity. These explanatory variables accounted for 52% and 84% of the variations in Chl-a of green algae and diatoms, and 10% and 21% of the variations in Fv/Fm of green algae and diatoms. When macrophytes was present, Chl-a and Fv/Fm of green algae and diatoms were significantly affected by electrical conductivity, TN, TP, and pH. These explanatory variables accounted for 39% and 77% of the variations in Chl-a of green algae and diatoms, and 43% and 36% of the variations in Fv/Fm of green algae and diatoms. Overall, nutrient availability and subsequently environmental changes caused more variations in phytoplankton Chl-a than variations in phytoplankton Fv/Fm, and more variations in diatoms than variations in green algae. Our results suggested that the response mechanism of phytoplankton to nutrient availability varied between the presence and absence of macrophytes, as well as between green algae and diatoms. Therefore, simultaneous evaluation of the biomass and physiological status of different phytoplankton groups can provide broader insight into the interaction mechanisms between macrophytes, nutrients and phytoplankton.